Isolated apical perfusion defect in SPECT-CT scans, is there any prognostic value?. (25th November 2020) - Lopes, J; Monteiro, M; Campos, D; Saleiro, C; Costa, S; Sousa, J; Puga, L; Gomes, A; Silva, J; Ferreira, M; Goncalves, L
Abstract: Background: Myocardial perfusion imaging (MPI) plays a significant role in diagnostic and therapeutic decision making in coronary artery disease (CAD). An isolated apical defect in the 17th segment in SPECT/CT scans is a common finding, sometimes attributed to the apical thinning phenomenon. However, the clinical significance of apical thinning or other isolated apical defects is unknown. Purpose: The purpose of this study is to assess the prognostic impact of an isolated apical perfusion defect (17th segment) in patients (P) with suspicion of significant CAD. Methods: A cohort of 612 consecutive P that underwent a MPI test with a SPECT/CT scanner, between January 2017 and December 2017, in a single nuclear medicine centre, was included in this retrospective study. The inclusion criteria for this study were either a normal perfusion exam (group 1 – G1) or only an isolated apical defect in the 17th segment, either reversible suggesting ischemia (group 2 – G2) or fixed suggesting necrosis (group 3 – G3). Images with and without attenuation correction were analysed. Mean follow-up was 29±4 months. The chi square test was used for categorical variables, and analysis of variance for continuous variables. Binary logistic regression was used to control for confounding. Results: A total of 612 P were included (57% male sex, mean age of 69±10) and divided in G1 (n=494, 80.7%), G2 (n=62, 10%) and G3 (n=56, 9.2%). P in G3 had higher body mass index (31±7, p=0.028) and higher prevalence of dyslipidemia (84%, p=0.001), while P in G1 had lower ejection fraction at rest (54±15, p=0.001). There was no association between the presence of isolated apical defect and all- cause mortality (G1 = 7.3% vs G2 = 6.5% vs G3 = 5.4%, p=0.851). There was a statistically significant difference between groups in the referral for coronary angiography in the bivariate analysis (G1 = 7.9% vs G2 = 35.5% vs G3 = 10.7%, p=0.001), but this association did not remain when accounted for potential confounders (angina, ejection fraction, previous CAD and diabetes) – OR=3.94, 95% CI: [0.968–16.093], p=0.056. In those P that underwent coronary angiography, there was no statistically significant difference between the 3 groups in revascularization of significant CAD (G1 = 38.5% vs G2 = 36.4% vs G3 = 50%, p=0.830). During the follow-up time, 11 P of group 1 suffered an acute coronary syndrome (ACS), but there were no events in group 2 or 3. Conclusion: Isolated apical myocardial defect on a SPECT/CT exam has no association with all-cause mortality in this patients. There is no significant difference in referral for coronary angiography or need for coronary revascularization between P with normal exams and P with isolated apical defects. Funding Acknowledgement: Type of funding source: None